Dinamika Penjatuhan Talak Melalui Whatsapp dalam Paradigma Pembaharuan Hukum Keluarga Islam - Ropei, Ahmad; Sururie, Ramdani Wahyu (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2021)
This article aims to describe the paradigm of Islamic family law reform against the dynamics of the imposition of divorce through WhatsApp media, one of the problems often faced in various divorce cases. This paper is classified as a qualitative type, with the approach used being library research. Data analysis was carried out using descriptive-analytical techniques. The results of this article indicate that the adoption of divorce via WhatsApp according to most legal scholars is valid with the qiyas approach as the delivery of divorce through writing in the form of a letter. Meanwhile, in the paradigm of reforming Islamic family law in Indonesia, the imposition of divorce via WhatsApp is considered invalid, considering that the validity of the divorce is only recognized when it is sworn in before the court. This paradigm is based on various efforts to achieve the benefit, especially to avoid arbitrary actions by the husband against his wife unilaterally in terms of imposing divorce and obtaining legal legality. [Artikel ini bertujuan menggambarkan paradigma pembaharuan hukum keluarga Islam terhadap dinamika penjatuhan talak melalui media WhatsApp yang menjadi salah satu persoalan yang seringkali dihadapi pada berbagai kasus perceraian. Tulisan ini tergolong ke dalam jenis kualitatif dengan pendekatan yang dipakai adalah studi kepustakaan (library research). Analisis data dilakukan dengan teknik deskriptif-analisis. Hasil penulisan artikel ini menunjukkan bahwa penjatuhan talak melalui WhatsApp dalam pandangan jumhur ulama hukumnya sah dengan argumentasi pendekatan qiyas sebagaiman penjatuhan talak melalui tulisan berupa surat. Sementara dalam paradigma pembaharuan hukum keluarga Islam di Indonesia, penjatuhan talak melalui WhatsApp dihukumi tidak sah, mengingat keabsahan talak hanya diakui ketika diikrarkan di hadapan sidang pengadilan. Paradigma ini didasarkan pada berbagai upaya meraih kemaslahatan, terutama dalam usaha menghindari tindakan semena-mena suami terhadap isteri secara sepihak dalam hal menjatuhkan talak dan juga untuk mendapatkan legalitas hukum, maka kehadiran ulil amri melalui sidang pengadilan dinilai sejalan dengan nilai-nilai kemaslahatan.]